Application of PIXE and PIGE methods for examination of tungsten and rhenium alloys obtained by CVD - Levenets, V.V.; Shchur, A.O.; Omelnyk, O.P.; Shirokov, B.M. (Functional Materials, 2007)
The use of nuclear phisics methods of ion beam analysis with registration of K-series X-ray and γ-ray from nuclear reactions for determination of tungsten, rhenium and fluorine in binary alloys obtained by chemical vapor deposition has been presented.